The mediating effect of operational risk management between business attributes and competitive advantage: exploratory study (survey) in the Iraqi Banking Sector - Falih, Falah Saleem (2022)
The banking industry generally, pay an important role in economic development of every country. The banking sector and financial institutions play a major role in determining economic growth worldwide. The Iraqi banking industry is still suffering from structural issues that must be resolved because of continuous economic and social loads and significant operational risks. The objective of this study to examine the mediating effect of the operational risk management between business attributes and the competitive advantage in the Iraqi banking sector. Thirteen hypotheses tailored by the theoretical lenses of the Resource-Based View (RBV) were proposed to test the theorised relationship of business attributes (Strategy, Technology, Human resources, Organisational structure), operational risk management, and the competitive advantage. A quantitative approach is used to obtain data from a survey (questionnaire) consisting of 60 items with a five-point Likert scale. A total of 114 executives and risk managers (80.2% response rate) in the Iraqi banking sector participated in the study. The data analysis was conducted using Smart PLS The findings of the path analysis of partial least squares (PLS) support variables in thay hypothesised direct relationships with a competitive advantage. The analysis results suggest that operational risk management partially mediates the relationship between business attributes (Strategy, Technology, Human resources, Organisational structure) and the competitive advantage. The results of this study contribute to the body of knowledge related to business attributes, operational risk management, and competitive advantage, which has not been thoroughly investigated in the literature. Besides the practical contribution, Highlighting the importance of the competitive advantage of banks by providing new ideas and perspectives related to essential tools such as business attributes (Strategy, Technology, Human resources, Organizational structure) and operational risk management in achieving the competitive advantage of the banking services sector.